Your answer would be D to double check out into a calculator 2 divided by 15 and it’s the same answer
Answer:
![V=196in^3](https://tex.z-dn.net/?f=V%3D196in%5E3)
Step-by-step explanation:
The volume of a pyramid is:
![V=\frac{A_{b}h}{3}](https://tex.z-dn.net/?f=V%3D%5Cfrac%7BA_%7Bb%7Dh%7D%7B3%7D)
where
is the area of the base and
is the height (the perpendicular measurement between base and highest point, not the slant height)
Since the base is a square, the area is given by:
where
is the length of the side:
, thus:
![A_{b}=(8in)^2\\A_{b}=64in^2](https://tex.z-dn.net/?f=A_%7Bb%7D%3D%288in%29%5E2%5C%5CA_%7Bb%7D%3D64in%5E2)
Now we need to find the height, for this we use the right triangle that forms with half of a square side (8in/2 = 4in), the slant height (10in), and the height.
In this right triangle, the slant height is the hypotenuse, the leg 1 is the unknown height, and leg 2 is half of the square side.
Using pythagoras:
![hypotenuse^2=leg1^2+leg2^2](https://tex.z-dn.net/?f=hypotenuse%5E2%3Dleg1%5E2%2Bleg2%5E2)
substituting our values, and indicating that leg 1 is height h:
![(10in)^2=h^2+(4in)^2](https://tex.z-dn.net/?f=%2810in%29%5E2%3Dh%5E2%2B%284in%29%5E2)
![100in^2=h^2+16in^2](https://tex.z-dn.net/?f=100in%5E2%3Dh%5E2%2B16in%5E2)
and solving for the height:
![h^2=100in^2-16in^2\\h^2=84in^2\\h=\sqrt{84in^2}\\ h=9.165in](https://tex.z-dn.net/?f=h%5E2%3D100in%5E2-16in%5E2%5C%5Ch%5E2%3D84in%5E2%5C%5Ch%3D%5Csqrt%7B84in%5E2%7D%5C%5C%20h%3D9.165in)
and finally we calculate the volume using this height and the area of the base:
![V=\frac{A_{b}h}{3}](https://tex.z-dn.net/?f=V%3D%5Cfrac%7BA_%7Bb%7Dh%7D%7B3%7D)
![V=\frac{(64in^2)(9.165in)}{3} \\V=195.5in^3](https://tex.z-dn.net/?f=V%3D%5Cfrac%7B%2864in%5E2%29%289.165in%29%7D%7B3%7D%20%5C%5CV%3D195.5in%5E3)
rounding to the nearest cubic inch: ![V=196in^3](https://tex.z-dn.net/?f=V%3D196in%5E3)
The constants of a polynomial is the term that has no variable attached to it.
<h3>The constant term</h3>
To determine the constant, we simply multiply the constant term in each factor of the polynomial.
So, we have:
<h3 /><h3>Polynomial P(x) = (x-2)(x-4)(x-5)</h3>
![Constant = -2 \times -4 \times -5](https://tex.z-dn.net/?f=Constant%20%3D%20-2%20%5Ctimes%20-4%20%5Ctimes%20-5)
![Constant = -40](https://tex.z-dn.net/?f=Constant%20%3D%20-40)
Hence, the constant is -40
<h3>Polynomial P(x) = (x-2)(x-4)(x+5)</h3>
![Constant = -2 \times -4 \times 5](https://tex.z-dn.net/?f=Constant%20%3D%20-2%20%5Ctimes%20-4%20%5Ctimes%205)
![Constant = 40](https://tex.z-dn.net/?f=Constant%20%3D%2040)
Hence, the constant is 40
<h3>Polynomial P(x) =1/2(x-2)(x-4)(x+5)</h3>
![Constant = \frac 12 \times -2 \times -4 \times 5](https://tex.z-dn.net/?f=Constant%20%3D%20%5Cfrac%2012%20%5Ctimes%20-2%20%5Ctimes%20-4%20%5Ctimes%205)
![Constant = 20](https://tex.z-dn.net/?f=Constant%20%3D%2020)
Hence, the constant is 20
<h3>Polynomial P(x) = 5(x-2)(x-4)(x+5)</h3>
![Constant = 5 \times -2 \times -4 \times 5](https://tex.z-dn.net/?f=Constant%20%3D%205%20%5Ctimes%20-2%20%5Ctimes%20-4%20%5Ctimes%205)
![Constant = 200](https://tex.z-dn.net/?f=Constant%20%3D%20200)
Hence, the constant is 200
<u>P(x) =-5(x-2)(x-4)(x+5)</u>
![Constant = -5 \times -2 \times -4 \times 5](https://tex.z-dn.net/?f=Constant%20%3D%20-5%20%5Ctimes%20-2%20%5Ctimes%20-4%20%5Ctimes%205)
![Constant = -200](https://tex.z-dn.net/?f=Constant%20%3D%20-200)
Hence, the constant is -200
Read more about polynomials at:
brainly.com/question/2833285
I dont know if those lines were suppose to be there, but i put 0.63 in simplest form = 63/100